EVALUASI DAN PENGEMBANGAN KNOWLEDGE MANAGEMENT SYSTEM MENGGUNAKAN POST-STUDY SYSTEM USABILITY QUESTIONNAIRE (PSSUQ) - Dhila Franzely Dhimas Putra (Institut Teknologi dan Bisnis (ITB) Swadharma, 2021)
Human resources are the most important asset as the main determinant of the company's success. Therefore, efforts to improve the effectiveness and performance of employees in a company are one of the important factors in improving company performance. This paper discusses how to evaluate the Knowledge management system and its development based on the evaluation results. The purpose of this study is to provide suggestions and directions for the development of KMS at PT. King Photo Group. The results of the analysis show that the performance of KMS is still not good at the interface, so it is necessary to focus on the development in that section. The author uses the PSSUQ (Post-Study System Usability Questionnaire) to evaluate and 8 Golden Rules as a reference at the development stage